Islamic content-based learning: Kindergarten illustrated narrative song "Lulu and Tom" - Suharsiwi, Suharsiwi; Lestari, Juwita Tri; Karim, Samuel (Assyfa Journal of Islamic Studies, 2024)
Music education during early life is crucial and has beneficial impacts on the development and maturation of children during this formative period. Music profoundly impacts young children as it fosters their cognitive capacities, language proficiency, motor skills, and imaginative thinking. Teachers must cultivate kids' gross motor abilities by providing opportunities for them to engage in movement activities and songs. This will enable children to experience movement and directly enhance their overall movement proficiency. This research aims to create songs inspired by Islamic illustrated stories that have been demonstrated to be valid and practical. The utilized development model is 4D, incorporating a Tessmer formative evaluation approach that encompasses needs analysis, product design, and assessment stages. The evaluation stages involve self-evaluation, expert review, one-to-one evaluation, and small-group evaluation. The data analysis technique employs walkthroughs, observations, and checklists. The research findings indicate that the average product and media validity is very valid. Three children were assessed individually during the one-to-one evaluation stage, whereas nine children were assessed together during the small group evaluation stage. The averages for the convenient category were derived from both stages. A practical method to cultivate a joyful ambiance during recreational pursuits is to engage in the auditory experience of music and singing. Songs can enhance children's language development, making the learning process easier. Thus, developing songs based on Islamic illustrated stories is pronounced valid, practical, and fit for use.